Diogo Antônio Feijó e Romualdo Antônio de Seixas: regalistas e romanizados na formação do Estado nacional brasileiro (1820-1840) - Gabriel Abilio de Lima Oliveira (2018)
Paying attention to the historical heterogeneity of intellectual formation and to the political action of the ecclesiastical hierarchys representatives and their partners, this work will privilege the study of two political and ecclesiological tendencies that began to draft in the First Kingdom and intensified their disputes during the Regencies. Each of these trends had priests at its leadership in the public sphere, namely, Regent Diogo Antônio Feijó, regent of the Brazilian Empire, and Archbishop Romualdo Antônio de Seixas. Feijó and Romualdo produced a vast intellectual repertoire and projected themselves on the coeval political scene. Concerning the chronological beacons of this work, the first two decades of the formation of the Brazilian national State are considered fundamental. That period witnessed the rise of the regalist clergyled by Feijó, along with the moderate liberal political group and also the dissension within this group. Between the two wings formed within the moderates, uncontrollable divergences became evident and nourished the conservative Regress. This movement had the leadership ofBernardo Pereira de Vasconcelos, having at his side D. Romualdo Seixas and other personalities linked to a counterrevolutionary, orthodox and Romanized clergy. Vasconcelos and Romualdo were among the protagonists of the fierce opposition undertaken to the regency of DiogoAntônio Feijó. Subsequent to the reforms of the Additional Act of 1834, the regressive offensive was fundamental to the creation of the Saquaremas political nucleus and to the genesis of the Conservative Party.